Numerical test of the method for revealing traces of deterministic chaos in the accreting black holes - Suková, Petra (2015)
The high energy radiation emitted by black hole X-ray binaries originates in an accretion disk, hence the variability of the lightcurves mirrors the dynamics of the disc. We study the time evolution of the emitted flux in order to find evidences, that low dimensional non-linear equations govern the accretion flow. Here we test the capabilities of our novel method to find chaotic behaviour on the two numerical time series describing the motion of a test particle around a black hole surrounded by a thin massive disc, one being regular and the other one chaotic.